Bicipital aponeurosis. Anatomical study and clinical implications() - Caetano, Edie Benedito (Rev Bras Ortop, 2017)
OBJECTIVE: The aim of this study was to analyze the anatomic variations of the bicipital aponeurosis (BA) (lacertus fibrosus) and its implications for the compression of the median nerve, which is positioned medially to the brachial artery, passing under the bicipital aponeurosis. METHODS: Sixty upper limbs of 30 cadavers were dissected, 26 of which were male and four, female; of the total, 15 had been previously preserved in formalin and glycerine and 15 were dissected fresh in the Laboratory of Anatomy. RESULTS: In 55 limbs, short and long heads of the biceps muscle contributed to the formation of the BA, and the most significant contribution was always from the short head. In three limbs, only the short head contributed to the formation of the BA. In two limbs, the BA was absent. The length of the bicipital aponeurosis from its origin to its insertion ranged from 4.5 to 6.2 cm and its width, from 0.5 to 2.6 cm. In 42 limbs, the BA was thickened; of these, in 27 it was resting directly on the median nerve, and in 17 a high insertion of the humeral head of the pronator teres muscle was found, and the muscle was interposed between the BA and the median nerve. CONCLUSION: These results suggest that a thickened BA may be a potential factor for nerve compression, by narrowing the space through which the median nerve passes.